Penyuluhan Kesehatan Lingkungan di SDN 2 Kersamenak Kecamatan Tarogong Kidul Kabupaten Garut - Novriyanti Lubis; Muhammad Fairuzzaman; Mike Agusti Nuryani; Bentang Yasha Muhammad Murki; Sri Putriany; Najwa Najiyya Arsyisyifa; Aprilia Sakinah; Rai Nurhalizah (ABDI: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
Early introduction of education about environmental health, especially for elementary school children, is very important. This is because schoolchildren are one of the groups most vulnerable to health problems. This counseling aims to increase the awareness of students at SDN 2 Kersamenak on environmental health. The socialization activity was carried out by providing counseling through media flayers and education in the form of environmental health materials directly to students at SDN 2 Kersamenak. Analysis of the level of students' understanding was identified through a survey method using 10 multiple choice test items based on three factors, namely understanding the definition and benefits of environmental health, and understanding of the characteristics of a good environment. In this school total 82 students, while only 42 students filled out the questionnaire. The survey results showed that 97.6% of students already understood the importance of environmental health even before the counseling was carried out. However, this socialization activity can also be said to be successful, because there is an increase in the percentage of knowledge of SDN 2 Kersamenak students about environmental health.